Tourism activity as an engine of growth: Lessons learned from the European Union - Velisaria Matzana; Aikaterina Oikonomou; Michael Polemis (Journal of Risk and Financial Management, 2022)
In this study, the linkage between tourism activity and economic development in 21 European countries is analyzed. The data are collected on an annual basis and cover the years from 1995 to 2017. The main purpose is to investigate empirically if there is a long-run connection between tourism activity and the development of the economy by applying a multivariate model. For this purpose, generalized method of moments (GMM) and Granger causality tests are applied within a panel data framework. The results reveal that tourism contributes significantly to European countries' economic growth. Furthermore, Granger causality analysis shows a unidirectional relationship between tourism and economic development, leading to sufficient evidence for the validity of the tourism-led-growth hypothesis. Therefore, for these European countries, the tourism-led growth hypothesis is supported (meeting our expectations).
Keywords: 650; economic growth; Europe; Granger causality; panel data; tourism